The Zika Virus: An Association to Guillain-Barré Syndrome in the United States - A Case Report - Rivera-Concepción, Joel R.; Betancourt, Jean P.; Cerra, Javier; Reyes, Edgardo (Puerto Rico Health Sciences Journal, 2018)
Case of a 37 year-old Puerto Rican male with no past medical history who was admitted to the hospital after developing paresthesia in the upper and lower extremities with associated skin rash, weakness, and dysautonomia. After rigorous analysis of the clinical patterns, neurologic manifestations, laboratory workups, CSF analysis, and nerve conduction studies we conclude the existence of a strong relationship between the Zika virus and the Guillain–Barré syndrome. The patient recovered promptly and his response to treatment was excellent.